Weed Control and Injury with Non-Labeled Herbicides in Grain Sorghum - R. S. Currie; P. W. Geier; W. Keeling; B. Bean (Kansas Agricultural Experiment Station Research Reports, 2018)
Palmer amaranth control at Garden City, KS, was good with Acuron or Lumax EZ. At Lubbock, TX, Palmer amaranth control was excellent with all herbicides except Surestart II and Valor at 1 oz/a. Surestart II and Valor provided only fair control of kochia and Russian thistle late in the season at Garden City. No visible sorghum injury from any herbicide was observed at Garden City, and sorghum yields were not affected. Very dry conditions during the experiment at Garden City likely minimized sorghum injury and limited sorghum yields. At Lubbock, minor sorghum injury was observed early with Acuron and Valor. Later in the season only Surestart II showed sorghum injury at Lubbock that translated into some yield loss. However, all herbicide-treated sorghum at Lubbock yielded 28 to 65 bu/a more grain than nontreated sorghum.
Keywords: residual control